Actinomycosis: report of a case with a persistent extraoral sinus tract - VAROL, ALTAN; GÖÇMEN, GÖKHAN (MOSBY-ELSEVIER, 2011)
Cervicofacial actinomycosis is a chronic suppurative and granulomatous infection that may reside for years and recur with sudden onset. It is the second most common type of actinomycosis and could be caused by trauma or infection. We report a draining actinomycotic sinus tract with extraordinary thickness that occurred owing to a long-standing chronic periapical infection of an extracted upper left second premolar 3 years before. (Oral Surg Oral Med Oral Pathol Oral Radiol Endod 2011;112:e121-e123)
Keywords: CERVICOFACIAL ACTINOMYCOSIS